A molar pregnancy detected by following irregular vaginal bleeding after a first trimester evacuation: rare case report - Salvi, Meena Bhati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
In this case report summarizes the sequence of events that led to detection of a molar pregnancy missed by ultrasound and initial pathology examination. A 29 years old Asian nulliparous patient came to our clinic with missed period. On beta HCG she was 6 weeks pregnant. After 20 days she was diagnosed with 7 weeks missed abortion on ultrasound. surgical evacuation done for same. After 3 weeks she came with irregular vaginal bleeding. After physical and vaginal examination Beta HCG done, which was very high. On transvaginal ultrasound partial molar pregnancy was detected, so she was immediately admitted and repeat surgical evacuation was done. Histopathology report confirmed partial molar pregnancy which was not detected in previous report. She was regularly followed up with Beta HCG value up to 1 year which declined dramatically. Though molar pregnancy is rare, but it has the potential to develop into invasive mole, so any abnormal bleeding post evacuation should be followed up properly. Beta HCG values and histopathological evaluation is important for correct diagnosis and follow up.